Frequency of Heart Diseases in Patients with Different Personality Types - Mathew, Schwan; Kalar, Musleh Uddin; Mujeeb, Effa; Hira Bibi, Kaniz; Zahid, Ruba Ali; Shaikh, Faizan; Hyder, Mahek; Mansoor, Farah; Ali, Uzma (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Heart disease as a leading cause of morbidity and mortality is of global concern. 17 million people die of Cardiovascular Diseases (CVD) each year. An impatient and over ambitious personality can develop heart disease. One’s nature determines one’s health condition. An easygoing and relaxed person leads a healthier life as compared to one who finds life difficult to handle. The NEO-PIR (NEO Personality Inventory) measures the five major domains of personality and also the traits that define each domain. Objective: To determine the different personality types of Cardiac patients at Karachi Institute of Heart diseases according to five factor model of personality (NEO PIR). Materials and Methods: This was a cross sectional study and non-probability convenient sampling was used and the Questionnaire NEO PIR was administered. Descriptive analyses was conducted and Chi Square test was used to determine the statistical significance in between the variable of Age, Neuroticism, Extraversion, Agreeableness, Openness and Conscientiousness. Results: Cross tab between Age and Agreeableness showed 32-50 year patients had low (60.4%), average (37.7%) and high (1.9%) agreeableness. Patients aged >51 had low (58.7%), average (37.3%) and high (4%) agreeableness with p-value 0.015. Conclusion: personality traits do have an impact on risk of cardiovascular disease. High neuroticism and low conscientiousness were found to be predominant in our patients.